Fuel oil production from thermal decomposition of the model and waste polystyrene: Comparative kinetics and product distribution - Ali, Ghulam; Nisar, Jan; Arshad, Muhammad (European Journal of Chemistry, 2023)
The thermal degradation of model polystyrene (MPS) and waste polystyrene (WPS) was performed in a thermobalance system at four heating rates (β) i.e., 5, 10, 15 and 20 °C/min in an inert atmosphere. The apparent activation energy (Ea) and frequency factor (A) for the MPS and the WPS were calculated using Ozawa-Flynn-Wall (OFW), Kissinger-Akahira-Sunose (KAS), and Augis-Bennetis (AB) methods. It has been determined that Ea and A vary according to fraction conversion, heating rates, and applied models. The activation energy determined for MPS was found to be in the range of 91-106, 90-105, and 114-133 kJ/mol, while, for WPS, Ea was determined in the range of 82-160, 79-159 and 102-202 kJ/mol by applying OFW, KAS, and AB models, respectively. From the results obtained, it was concluded that the Ea determined by all of these methods increases with fraction conversion, indicating that the decomposition of polystyrene follows a complex mechanism of the solid-state reaction. Hence, the kinetic parameters, i.e., Ea and A, seem to play a key role in investigating the mechanism of solid-state reactions and will provide an opportunity to develop the mechanism of the industrial decomposition reactions. The results show that the MPS has a lower activation energy compared to WPS. This high Ea of WPS may be due to the additives used in the manufacturing of different polystyrene products. Pyrolysis GC/MS of WPS indicates that the main components of pyrolysis oil are 1-hydroxy-2-propanone, styrene, α-methyl styrene, toluene, and 1,2-dimethyl benzene. The presence of some oxygenated compounds in the fuel oil of WPS may be due to contamination or additives used during polystyrene processing, as the WPS samples were collected from a garbage dump near a local market. WPS can be utilized as fuel if the fuel oil collected from the pyrolysis of WPS is properly upgraded to make it equivalent to commercial fuel oil.